A new Octomeria (Orchidaceae: Pleurothallidinae) and nomenclatural notes for related Southern Brazilian species - Dos Santos, Thiago Faria [UNESP]; De Brito, Antonio Luiz Vieira Toscano; De Camargo Smidt, Eric (Magnolia Press, 2022)
Octomeria imigiae is proposed as a new species from the Atlantic Rainforest of South Brazil. It is described, illustrated, and compared with sympatric and similar species. An identification key is provided. The new species is recognised by its reptant growth habit and tiny yellow flowers. It is similar to Octomeria chamaeleptotes and several other terete-leaved species from which it can be easily distinguished by its vegetative and floral morphology. Octomeria riograndensis and Octomeria sancti-angeli are proposed as new synonyms of Octomeria chamaeleptotes, and typification designations for this complex are made.
Keywords: Diversity; Flora of Brazil; Orchidaceae; Taxonomy